PI3K inhibition in breast cancer: Identifying and overcoming different flavors of resistance. (June 2021) - Vitale, Silvia Rita; Martorana, Federica; Stella, Stefania; Motta, Gianmarco; Inzerilli, Nicola; Massimino, Michele; Tirrò, Elena; Manzella, Livia; Vigneri, Paolo
Graphical abstract: Highlights: Aberrant PI3K activation determines deregulation of the PI3K/AKT/mToR pathway. PIK3CA mutations exert both a prognostic and predictive role in breast cancer. Several biological mechanisms confer resistance to PI3K inhibition in breast cancer. Combination regimens might effectively overcome resistance to PI3K inhibition. Abstract: The phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway is commonly deregulated in many human tumors, including breast cancer. Somatic mutations of the PI3K alpha catalytic subunit ( PIK3CA ) are the most common cause of pathway hyperactivation. Hence, several PI3K inhibitors have been investigated with one of them, alpelisib, recently approved for the treatment of endocrine sensitive, PIK3CA mutated, metastatic breast cancer. Unfortunately, all patients receiving a PI3K inhibitor eventually develop resistance to these compounds. Mechanisms of resistance include oncogenic PI3K alterations, pathway reactivation through upstream or downstream effectors and enhancement of parallel pro-survival pathways. We review the prognostic and predictive role of PI3K alterations in breast cancer, focusing on resistance to PI3K inhibitors and on biomarkers with potential clinical relevance. We also discuss combination strategies that may overcome resistance to PI3K inhibitors, thus increasing the efficacy of these drugs in breast cancer.